The Utilization of Quality Improvements in Public Health Systems Across Asian Countries : A Systematic Review - Rudi Nasib; Nelson Lean Boon Leong; Muhammad Mudassir Abdul Rahim; Nachia Banu Abdul Rahim; Nabihah Ali; Mohd Ihsanuddin Abas; Amirah Azzeri; Hafiz Jaafar; Mursid Raharjo; Nur Ezdiani Mohamed; Abdul Rahman Ramdzan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Malaysian Journal of Medicine and Health Sciences Volume: 19(Supp 20) page: 186-195